Radiologic overview of sinonasal lesions - Syed, Mohammed U.; Stephen, Steve J.; Rahman, Akm A. (Frontiers in Radiology, 2024)
Sinonasal tumors are often malignant and comprise approximately 3% of all head and neck malignancies. Half of these tumors arise in the nasal cavity, and other common locations of origin include the ethmoid and maxillary sinuses. Some unique clinical features are anosmia and altered phonation but the most common general features include headache, epistaxis, and diplopia. CT and MRI may be used to assess tumor location, invasion of adjacent tissue, presence of metastasis, internal tumor heterogeneity, and contrast enhancement. Local invasion of the tumor beyond the sinonasal tract can impact adjacent structures such as the cranial nerves, skull base, branches of the internal carotid artery, and orbit leading to neurologic signs, facial pain, and diplopia. Imaging is used in the diagnosis, staging, and treatment planning of sinonasal tumors. This collection of benign and malignant sinonasal tumors will include some rare and unique cases with an emphasis on imaging features demonstrating a wide variety of pathologies.